Rice root growth and development in competition with weedy rice - E. Schaedler,Carlos (2020)
Abstract Background: Weedy rice belongs to the same taxon as irrigated rice (Oryza sativa L.), and is the main weed of the crop. However, it exhibits different traits that produce greater competitive capacity using solar radiation. In competition for light, plants invest in photoassimilates for the shoots and can reduce their root development. Objectives: The objective of this work is to evaluate the initial growth of weedy and cultivated rice roots in response to light competition. Methods: The experiment was conducted in a greenhouse (hydroponic system), using a completely randomized design, arranged in a 2x2x6 factorial scheme, with five replications. Factor A consisted of the weedy rice biotype Q35B and the rice cultivar IRGA 424; factor B of light competition conditions (presence or absence of 75 weedy rice plants); and factor C of assessment time. At 0, 7, 14, 21, 28 and 35 days after transplanting, samples were taken from each experimental unity to measure the root area, perimeter, length, number of tips, and root dry weight (RDW), and shoot dry weight (SDW). Results: Competition for light reduced the area, perimeter, length, number of root tips, reduced the RDW and the SDW of both, the weedy rice biotype and crop rice. However, regardless of the competitive condition, the weedy rice showed a higher area, perimeter, initial growth, number of tips, RDW and SDW than that of cultivated rice. Conclusion: Weedy rice exhibits greater competitive capacity using the resources beneath the soil.